PELATIHAN ENGLISH FOR SPECIFIC PURPOSE UNTUK SISWA TEKNIK KOMPUTER DAN JARINGAN DI KABUPATEN TANGERANG - Rosari, Maria Dewi (LPPM Universitas Islam 45 Bekasi, 2025)
The English for Computing training program at SMK Jaya Buana aims to enhance students' communication skills in a professional context through the English for Specific Purposes (ESP) approach. This program is specifically designed for students in the Computer and Network Engineering (Teknik Komputer dan Jaringan, TKJ) department to help them understand technical terminology in English and use technical vocabulary in the language skills required in the field of computer and network engineering. The training consists of six stages: introduction, opening, vocabulary building, product analysis, practice, and closing, implemented using a scaffolding instructional strategy to ensure gradual and systematic learning. Additionally, interactive methods such as digital games, case studies, and presentation sessions are applied to increase student participation and comprehension. Evaluation results indicate a significant improvement in students' mastery of technical vocabulary and their English-speaking skills. Therefore, this training can serve as an effective learning model for other vocational schools seeking to implement the ESP approach in English instruction in a more contextual and applicable manner.